Somatic, Auditory, Visual and Intellectual (SAVI) Learning Models Affect Students 'Mathematics Learning Achievement - Fajriah, Leni; Nurfitriani, Meiliana; Permana, Rahmat (Universitas Pendidikan Ganesha, 2020)
The low mathematics learning achievement of students due to the less than optimal use of innovative learning models makes it difficult for students to understand the learning material as the reason why this study was conducted. The purpose of this study was to analyze the effect of the application of Somatic, Auditory, Visual and Intellectual (SAVI) learning. This type of this study was expresearcherimental research, with quantitative data. This study used the experimental design of The Non-Equivalent Group Design. The population of this study were all students of class V, amounting to 61 students. The technique in determining the research sample is random sampling. Test and interview methods were used in collecting research data. The results of data analysis showed that the average mathematics learning achievement of students in the group given the SAVI learning model got 83.6 results while the average mathematics learning achievement of students in the conventional taught group got 61.66 results. The difference can also be seen from the average N gain, namely the experimental class is 0.68 in the quite effective category, while for the average N gain, and the control class is 0.22, in the ineffective category. Thus, there is a significant difference in students' mathematics learning achievement between the experimental class that uses the SAVI learning model and the control class that does not use the SAVI learning model.